One-Pot Three-Component Synthesis and Molecular Docking of Some Novel 2-Thiazolyl Pyridines as Potent Antimicrobial Agents - Abdelrazek, Fathy M.; Gomha, Sobhi M.; Shaaban, Mohamed E.B.; Rabee, Kamal A.; El-Shemy, Heba N.; Abdallah, Abanoub M.; Metz, Peter (Mini Reviews in Medicinal Chemistry, 2019)
Background: Thiazoles and pyridines are versatile synthetic scaffolds possessing wide spectrum of biological effects including potential antimicrobial activity. Objective: In the efforts to develop suitable antimicrobia drugs, medicinal chemists have focused on thiazole derivatives. A novel series of 2-thiazolyl pyridines was prepared in a one-pot three-component reaction using 2-bromoacetyl pyridine as a starting precursor. Method: Structure of the synthesized compounds was elucidated by spectral data (FT-IR, 1H NMR, 13C NMR, and mass) and elemental analyses. The prepared compounds were screened for their in vitro antimicrobial activity. Results: The results revealed that compounds 4a,b,e-g and 12 showed promising activity. Molecular docking studies using MOE software were carried out for compounds 4a and 4b which exhibited potent activities indicated by the diameter zones (4a; 3.6, 4.0, 1.2 mm) (4b; 4.2, 3.5, 1.5 mm) and the binding affinities (4a; -5.7731, -5.3576, -4.6844 kcal mol-1) (4b; -5.9356, -2.8250, -5.3628 kcal mol-1) against Candida albicans, Bacillus subtilis and Escherichia coli, respectively. Conclusion: This paper describes a facile and efficient MCR for synthesis of 2-thiazolyl pyridines from reaction of 2-bromoacetyl pyridine with different reagents. There was an agreement between the values of binding affinities and interactions and the data obtained from the practical antimicrobial screening of the tested compounds.
Keywords: thiazoles